Role of echocardiographic dyssynchrony parameters in predicting response to cardiac resynchronization therapy. Issue 11 (November 2015) - Maffè, Stefano; Paffoni, Paola; Dellavesa, Pierfranco; Perucca, Antonello; Kozel, Daniela; Paino, Anna M.; Cucchi, Lorenzo; Zenone, Franco; Bergamasco, Luca; Pardo, Nicolò Franchetti; Signorotti, Fabiana; Baduena, Lara; et al.
Abstract : Aims: In the present study, we compare different echocardiographic cardiac dyssynchrony parameters, both of intraventricular and interventricular dyssynchrony, in order to predict response to cardiac resynchronization therapy (CRT). Methods and results: In a population of 77 heart failure patients scheduled for CRT, we measured the interventricular mechanical delay (IVMD) and we analyzed six different parameters of intraventricular dyssynchony: the tissue Doppler imaging (TDI) septum-lateral wall delay, the systolic dyssynchrony index; the three-dimensional SD of the time to reach minimum systolic volume for 16 left ventricular segments (3D-SDI); the speckle-tracking radial, circumferential and longitudinal dyssynchrony. At 6 months of follow-up, 61 (79%) patients were responders (⩽15% in left ventricular end-systolic volume). On baseline analysis, 3D-SDI, radial strain, longitudinal strain and circumferential strain and IVMD were significantly higher in responder group (10.8 ± 3.9 vs. 7.6 ± 1.8% for 3D-SDI; P = 0.003; 212 ± 91 vs. 125 ± 36 ms for radial strain, P = 0.0003; 185 ± 83 vs. 134 ± 53 ms for longitudinal strain, P = 0.02; 190 ± 80 vs. 130 ± 54 ms for circumferential strain, P = 0.006; 45 ± 21 vs. 30 ± 20 ms for IVMD; P = 0.01). On univariate and multivariate analysis, only IVMD was significantly associated with a complete echocardiographic response to CRT. 3D-SDI and radial strain present the better values of sensitivity and specificity, overall if associated to an evaluation of IVMD (sensitivity 76%, specificity 88%, for 3D-SDI + IVMD; sensitivity 80% and specificity 85% for radial strain + IVMD). Conclusion: The novel parameters, such as 3D-SDI and speckle-tracking (particularly radial strain), offer better diagnostic accuracy in identifying patients who are responders to CRT. The addition of the contemporary parameter of IVMD improves the diagnostic accuracy.